2021
DOI: 10.1158/1078-0432.ccr-20-4928
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Baseline and On-Treatment Glycemia on Everolimus-Exemestane Efficacy in Patients with Hormone Receptor–Positive Advanced Breast Cancer (EVERMET)

Abstract: We conducted a multicenter, retrospective, Italian study to investigate the impact of baseline and on-treatment (i.e., during first three months of therapy) blood glucose levels on progression-free survival (PFS) in HR+/HER2-aBC patients treated with EVE-EXE. Results:We evaluated 809 HR+/HER2-aBC patients treated with EVE-EXE as any-line of therapy for advanced disease. When evaluated as dichotomous variables, baseline and on-treatment glycemia were not significantly associated with PFS. However, when blood gl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Anyway, in an exploratory analysis, we found no PFS differences in patients presenting with stage IV versus relapsing disease, overall and per treatment arm (data not shown). Recent data from Vernieri et al [24] have demonstrated an impact of on-treatment glycaemia on everolimus efficacy In our study, very few patients experienced hyperglycaemia, not allowing for statistical analysis.…”
Section: Discussionmentioning
confidence: 63%
“…Anyway, in an exploratory analysis, we found no PFS differences in patients presenting with stage IV versus relapsing disease, overall and per treatment arm (data not shown). Recent data from Vernieri et al [24] have demonstrated an impact of on-treatment glycaemia on everolimus efficacy In our study, very few patients experienced hyperglycaemia, not allowing for statistical analysis.…”
Section: Discussionmentioning
confidence: 63%
“…Thus, it is possible that the effects of inter-individual variability and concomitant drug treatment on hyperglycemia are more pronounced in patients who are not taking DM drugs than in patients who are taking them. In fact, Vernieri et al (21) recently reported that patients who are normoglycemic at baseline and experience treatment-induced DM have lower progression-free survival than patients who are already hyperglycemic at baseline and experience breast cancer treatment-induced DM. Therefore, in the absence of concomitant DM drug treatment, these patterns suggest that patients who develop DM early in treatment may have poor DM outcomes and require prompt treatment, especially considering that everolimus-induced hyperglycemia can also induce drug resistance in cancer cells (14).…”
Section: Discussionmentioning
confidence: 99%
“…Metabolites of fat (e.g., Palmitic acid) CD36 [199,203] Metabolites of protein (e.g., Insulin-like growth factor 1) IGF-1 Receptor [204] Metabolites of carbohydrate (e.g., Glucose) Hexokinase 2 (HK2) [205] Hormone receptor-negative (HR-) Piperine HER2 [13,135,184] Metabolite of alcohol (e.g., Acetaldehyde) Estrogen Receptor (ER) [206] 2-amino-4-cyano butanoic Aromatase [107] Alpha-Tocopherol HER2 [190] Metabolites of fat (e.g., Palmitic acid) CD36 [207] Metabolites of protein (e.g., Insulin-like growth factor 1) IGF-1 Receptor [201] Metabolites of carbohydrate (e.g., Glucose) Hexokinase 2 (HK2) [208]…”
Section: Summary Of Current Research Linking Diet-related Metabolites...mentioning
confidence: 99%